THE ROLE OF THE ACADEMIC TUTOR IN THE PERSONALITY DEVELOPMENT OF FUTURE PHARMACISTS - Kropelnytska, Yulia; Velyka, Alla; Yakymchuk, Vira (SWorldJournal, 2022)
Nowadays, the primary focus of the educational process is concentrated on enhancing the professional qualities of students, their personal growth, the formation of ideological guidelines, and the best human traits, i.e., conscience, decency, intelligence,